Tribology and biophysics of artificial joints - Pinchuk, L. S. (Leonid Semenovich); ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2006)
Joint endoprosthetics - the science of implanting artificial joints into the human body - has been around since the 1960s, and consistent advancements are leading to better practice, materials and mechanics. The present book is devoted to the biophysics and effect of wear, friction and lubrication on artificial joints. The important aspects of biocompatibility and wear resistance are reviewed and a retrospective analysis of modern joint endoprosthetic designs is presented. Data on clinical aspects of endoprosthetics are cited in support of the text. Advancements in genetic engineering, and promising new techniques of designing bone and cartilage transplants are explored, and a critical comparison between tribological mechanisms of operation and natural joint functioning are made. An exceptional resource for all specialists in orthopedy, biophysics, immunology and engineers engaged in developing artificial joints.
Arthrology and joint endoprosthetics -- Materials for joint endoprostheses -- Designs of joint endoprostheses -- Some clinical aspects of endoprosthetics -- Tribological aspects of endoprosthetics -- Simulation of the cartilage tissue -- Simulation of biopotentials in joints -- Advances in joints endoprosthetics.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Artificial joints -- Design; Artificial joints -- Materials; Tribology; Arthroplasty, Replacement; Joint Prosthesis; Biocompatible Materials; Biophysics; Prosthesis Design; MEDICAL -- Allied Health Services -- Medical Technology; Artificial joints -- Design; Artificial joints -- Materials; Tribology; Electronic books